2002
DOI: 10.1207/s15326985ep3702_4
|View full text |Cite
|
Sign up to set email alerts
|

Academic Emotions in Students' Self-Regulated Learning and Achievement: A Program of Qualitative and Quantitative Research

Abstract: Academic emotions have largely been neglected by educational psychology, with the exception of test anxiety. In 5 qualitative studies, it was found that students experience a rich diversity of emotions in academic settings. Anxiety was reported most often, but overall, positive emotions were described no less frequently than negative emotions. Based on the studies in this article, taxonomies of different academic emotions and a self-report instrument measuring students' enjoyment, hope, pride, relief, anger, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

152
2,479
13
172

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,839 publications
(3,015 citation statements)
references
References 52 publications
152
2,479
13
172
Order By: Relevance
“…Le rôle des émotions dans le fonctionnement cognitif : les modèles de Pekrun, de Bandura et de Kuhl C'est assez unanimement que les chercheurs en cognition, en motivation et en éducation reconnaissent l'importance des émotions associées aux situations d'apprentissage et leur influence sur l'engagement cognitif et l'apprentissage (Bandura, 1986;Boekaerts, 1993;Govearts, 2006;Linnenbrink et Pintrich, 2004;Pekrun, Goetz, Titz et Perry, 2002). Certains s'y sont arrêtés plus spécifiquement et leur ont fait une place importante dans leur théorie.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Le rôle des émotions dans le fonctionnement cognitif : les modèles de Pekrun, de Bandura et de Kuhl C'est assez unanimement que les chercheurs en cognition, en motivation et en éducation reconnaissent l'importance des émotions associées aux situations d'apprentissage et leur influence sur l'engagement cognitif et l'apprentissage (Bandura, 1986;Boekaerts, 1993;Govearts, 2006;Linnenbrink et Pintrich, 2004;Pekrun, Goetz, Titz et Perry, 2002). Certains s'y sont arrêtés plus spécifiquement et leur ont fait une place importante dans leur théorie.…”
Section: Introductionunclassified
“…Voulant cibler en particulier les émotions liées au fonctionnement scolaire, Pekrun et ses collaborateurs (Pekrun, 2006;Pekrun et al, 2002) ont proposé une théorie sociocognitive des émotions « académiques ». Ce modèle met l'accent sur des liens présumés entre des caractéristiques environnementales (qualité de l'enseignement, valeurs privilégiées, rétroaction, etc.)…”
Section: Introductionunclassified
“…Even though positive emotions are described about as often as negative emotions among students, anxiety is the most commonly reported emotion related to exam-taking (Pekrun, Goetz, Titz & Perry, 2002). Performance in achievement situations is known to be increased by positive motivation (Rand, Lens & Decock, 1991), but for example Wolf and Smith (1995) found that high motivation in combination with high anxiety produced almost the same levels of performance as low motivation in combination with low anxiety.…”
Section: The Trends In International Mathematics and Science Study -Tmentioning
confidence: 99%
“…Although Pekrun et al, (2002) caution against simplistic accounts of bad-good, research has tended to focus on negative emotions with less attention devoted to the 'deliberate design and maintenance of positive learning environments' in higher education (Moore & Kuol, 2007: 88): the tendency is to 'overlook and even ignore positive emotions' (Tugade & Fredrickson, 2002: 320), 'placing more emphasis on the problem perspective' in research for example on transition (Palmer et al, 2009: 39).…”
Section: Positive Emotions In Teaching Learning and Assessmentmentioning
confidence: 99%
“…Such positive emotions appear associated with 'desire', to get, want or to know something. They appear as activating emotions, with desire seen as pleasure associated with fulfilling a lack or need, followed by motivating action (Pekrun et al, 2002).…”
Section: Pedagogic Activity: Doing Getting and Knowingmentioning
confidence: 99%